A possible explanation of the 'Exchange Rate Disconnect Puzzle': a common solution to three macroeconomic puzzles?. Issue 13 (29th July 2017) - Horioka, Charles Yuji; Ford, Nicholas
ABSTRACT: Meese and Rogoff (1983) and subsequent studies find that economic fundamentals are apparently not able to explain exchange rate movements, but we argue that this so-called 'Exchange Rate Disconnect Puzzle' arose because researchers such as Meese and Rogoff (1983) did not use the right fundamentals and because they did not allow for the forward-looking nature of exchange rate determination. Further, because they apparently were not aware that financial markets by themselves could not equalize interest rates across countries, they did not properly appreciate that the exchange rate is strongly influenced by agents' expectations of aggregated differences in local returns. Thus, we believe that the same underlying explanation provided by Ford (2015) and Ford and Horioka (2016a, 2016b) for the Feldstein-Horioka (1980) Puzzle and the PPP Puzzle – namely that financial markets alone cannot achieve net transfers of financial capital and cannot equalize real interest rates across countries – also helps explain why previous attempts to connect changes in the exchange rate to economic fundamentals have not been successful and so can also be said to contribute to solving the Exchange Rate Disconnect Puzzle.